An Accessory Protein Is Required for Relaxosome Formation by Small Staphylococcal Plasmids - Smith, Matthew C. A. (American Society for Microbiology, 2004)
Mobilization of the staphylococcal plasmid pC221 requires at least one plasmid-encoded protein, MobA, in order to form a relaxosome. pC221 and closely related plasmids also possess an overlapping reading frame encoding a protein of 15 kDa, termed MobC. By completing the nucleotide sequence of plasmid pC223, we have found a further example of this small protein, and gene knockouts have shown that MobC is essential for relaxosome formation and plasmid mobilization in both pC221 and pC223. Primer extension analysis has been used to identify the nic site in both of these plasmids, located upstream of the mobC gene in the sense strand. Although the sequence surrounding the nic site is highly conserved between pC221 and pC223, exchange of the oriT sequence between plasmids significantly reduces the extent of relaxation complex formation, suggesting that the Mob proteins are selective for their cognate plasmids in vivo.